EspI regulates the ESX‐1 secretion system in response to ATP levels in Mycobacterium tuberculosis. Issue 5 (31st July 2014) - Zhang, Ming; Chen, Jeffrey M.; Sala, Claudia; Rybniker, Jan; Dhar, Neeraj; Cole, Stewart T.
Summary The function of EspI, a 70 kDa protein in Mycobacterium tuberculosis, has remained unclear. Although EspI is encoded by a gene within the esx‐1 locus, in this study we clarify previous conflicting results and show that EspI is not essential for ESX‐1‐mediated secretion or virulence in M. tuberculosis. We also provide evidence that reduction of cellular ATP levels in wild‐type M. tuberculosis using the drug bedaquiline completely blocks ESX‐1‐mediated secretion. Remarkably, M. tuberculosis lacking EspI fails to exhibit this phenotype. Furthermore, mutagenesis of a highly conserved ATP‐binding motif in EspI renders M. tuberculosis incapable of shutting down ESX‐1‐mediated secretion during ATP depletion. Collectively these results show that M. tuberculosis EspI negatively regulates the ESX‐1 secretion system in response to low cellular ATP levels and this function requires the ATP‐binding motif. In light of our results the potential significance of EspI in ESX‐1 function during latent tuberculosis infection and reactivation is also discussed.